Evaluasi Mutu dan Keamanan Pakan Ayam Petelur Masa Produksi di Kabupaten Tasikmalaya : The Evaluation of Feed Quality and Feed Safety for Layer in Tasikmalaya Regency - Hakim, Lukmanul; Laconi, Erika B.; Hermana, Widya (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study aims to evaluate the suitability of the quality and safety of feed for layer with the Indonesian National Standard (SNI) as an effort to maintain the quality of feed circulating in Tasikmalaya Regency. This study focuses on the SNI criteria for feed for leyer SNI 8290.5:2016. Sampling of layer was carried out at the center of layer farms in Tasikmalaya Regency, namely Padakembang District, Sukaratu District, Cibalong District, Karangnunggal District, Pagerageung District, Rajapolah District and Kadipaten District. The parameters tested were water, ash, crude protein, crude fat, crude fiber, calcium, phosphorus and aflatoxin. The average analysis results for these parameters are still in accordance with SNI based on the test uncertainty figures, the results of the ash analysis were 14.17% with a test uncertainty figure for ash of ±0.23% and aflatoxin 51.32 µg kg-1 with a test uncertainty figure for aflatoxin of ±3.07µg kg-1. The overall test results in Tasikmalaya Regency, for the test parameters of ash, crude protein, crude fat, calcium and aflatoxin were equally high for non compliance with the applicable SNI with the highest proportion above 25% of the total samples. The test parameters of factory feed that did not comply with SNI were ash, calcium and aflatoxin, for Poultry Shop (PS) test parameters that did not comply with SNI were ash, protein, calcium and aflatoxin while for farmer test parameters that did not comply with SNI were ash, protein, crude fat, calcium and aflatoxin. The high non-compliance of SNI in these test parameters shows how important it is to monitor and control the quality and safety of feed strictly to ensure that the feed given to livestock meets the established nutritional standards. Key words: feed, laboratory, layer, quality, standard